FINANCING MICRO AND SMALL ENTERPRISES: ASSESSING THE IMPACT OF MUDRA LOANS IN AN EMERGING ECONOMY - Mahajan, Yogesh (Indian Journal of Finance and Banking, 2021)
This paper studies the impact of mudra on small and micro enterprises in terms of income generation, business expansion, standard of living, and employment generation in the process. The research is socio-economic research. The project applied mean difference method for quantitative data analysis and relative importance index method to analyse qualitative data. Paper used Schedule to conduct personal interviews to collect data from 384 respondents using convenience sampling. It was found that to some extent, the schemes have been successful in providing loans to MSME sector. The enterprises are benefitted due to collateral free mudra loan in terms of income generation and business expansion. But there was no significant impact on employment generation and standard of living as proved from the data collected from the respondents due to mudra loan. Also, no significant improvement in human development index was found among the respondents. No significant improvements in quality of food and nutrition were found as informed by the respondents. Financial independence has not been achieved for the women entrepreneurs. Policy implications for government and bank has been discussed at the end of paper. The paper is based on the project funded by Indian Council of Social Science Research, New Delhi. This is a first kind of study conducted to study the impact of mudra loans on small and micro enterprises in India. JEL Classification Codes: M10, E21.